2021
DOI: 10.17323/jle.2021.11240
|View full text |Cite
|
Sign up to set email alerts
|

Exploring How Rhetorical Organization Contributes to the Readability of Essays

Abstract: The facilitative benefits of genre-specific reading have often been cited as a truism in the field of writing education. In line with this, writing center self-access libraries typically provide a selection of composition texts, including rhetorics (anthologies of model paragraphs and essays). Readability formulae (e.g., the Lexile Readability Formula) are often used to determine whether these texts will be a good fit for potential readers, and although the Lexile Formula reliably and validly assesses two feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Signal words did not significantly affect text difficulty, which is in alignment with research that has found that signal words do not affect students' reading comprehension (Meyer, 1975), but not with research that argues the importance of signal words (Baker, 2021;Van Silfhout et al, 2014) or research that states that signal words affect students' understanding of texts (Aidinlou & Pandian, 2011;Al-Surmi, 2011;Miccinati, 1975;Roen, 1984;Xu et al, 2019). Furthermore, signal words did not mediate the relationship between rhetorical organization and paragraph structure, contrary to previous literature that argues signal words assist readers in forming a mental representation of the relationships within a text (Xu et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Signal words did not significantly affect text difficulty, which is in alignment with research that has found that signal words do not affect students' reading comprehension (Meyer, 1975), but not with research that argues the importance of signal words (Baker, 2021;Van Silfhout et al, 2014) or research that states that signal words affect students' understanding of texts (Aidinlou & Pandian, 2011;Al-Surmi, 2011;Miccinati, 1975;Roen, 1984;Xu et al, 2019). Furthermore, signal words did not mediate the relationship between rhetorical organization and paragraph structure, contrary to previous literature that argues signal words assist readers in forming a mental representation of the relationships within a text (Xu et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…That is, some text types are more complex than others, learners’ awareness can affect understanding (Flick & Anderson, 1980), and rhetorical structures are not constant across cultures (Kaplan, 1966, 2005). Nevertheless, taxonomy explorations have attempted to provide as distinctive a picture as possible (see Alkhaleefah, 2017; Amiri et al, 2012; Baker, 2021; Carrell, 1984a; Freedle & Kostin, 1991, 1993; Goh, 1990; Lei, 2010; Meyer & Freedle, 1984; Putra, 2012; Saadatnia et al, 2016; Salmani, 2010; Sharp, 2002; Talbot et al, 1991; Yali & Jiliang, 2007; Zhang, 2008). However, the results have generally been incongruent due mostly to varying text types under study, methodology, and participants’ reading levels (Baker, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations